2019
DOI: 10.1177/0198742919839221
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coaching on Teacher-Delivered Behavior-Specific Praise in Pre-K–12 Settings: A Systematic Review

Abstract: In this systematic literature review, we examined the effects of coaching (e.g., written, emailed, visual, video, and self-monitored performance feedback; in vivo bug-in-ear prompting; combinations) teachers and other educators to increase their use of behavior-specific praise, a low-intensity teacher-delivered strategy previously determined to be a potentially evidence-based practice based on Council for Exceptional Children’s (CEC) Standards for Evidence-Based Practices in Special Education. Research has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 77 publications
(123 reference statements)
2
31
0
Order By: Relevance
“…Teacher praise has been established as a naturalistic and simple evidence-based strategy to encourage prosocial behaviors and reduce problem behaviors in the classroom (Ennis et al, 2018(Ennis et al, , 2019. Findings from a literature review on teachers' use of behavior-specific praise (BSP) in K-12 traditional school-based settings indicated increases in student on-task behavior, decreases in inappropriate behaviors, and reduced student tardiness (Royer et al, 2019).…”
Section: Evidence Supporting Teacher Praise With Middle and High Schomentioning
confidence: 99%
“…Teacher praise has been established as a naturalistic and simple evidence-based strategy to encourage prosocial behaviors and reduce problem behaviors in the classroom (Ennis et al, 2018(Ennis et al, , 2019. Findings from a literature review on teachers' use of behavior-specific praise (BSP) in K-12 traditional school-based settings indicated increases in student on-task behavior, decreases in inappropriate behaviors, and reduced student tardiness (Royer et al, 2019).…”
Section: Evidence Supporting Teacher Praise With Middle and High Schomentioning
confidence: 99%
“…Royer, Lane, Dunlap, and Ennis (2018) applied Council for Exceptional Children (CEC; 2014) standards for evidence-based practices with six studies and found teacher-delivered BSP to be a potentially evidence-based practice , citing the need for more methodologically rigorous studies with three or more participants to add to the evidence base. Extending their systematic literature review, Ennis, Royer, Lane, and Dunlap (2018) applied CEC (2014) quality indicator standards to 44 studies (in 41 articles) focused on coaching educators to increase BSP and determined the practice to be evidence based. An encouraging finding in the literature on BSP was its ease of application in multiple grades and settings.…”
Section: Behavior-specific Praise: Supporting Evidencementioning
confidence: 99%
“…When student outcome data were reported, improvements were noted in student behavior. In a separate study, Ennis and colleagues (2019b) found that BSP delivery improved student behavioral performance, increased engagement, and decreased disruptive behaviors. Furthermore, that study (Ennis et al, 2019b) suggested that BSP can be a strategy for different types of students, which was attributed to the large number of students who participated in BSP interventions, including those at risk of being identified as having an emotional and/or behavioral disability (EBD) and those at risk of academic failure.…”
Section: Bspmentioning
confidence: 93%
“…To implement and subsequently deliver high levels of BSP in the classroom, teachers, paraprofessionals, and other stakeholders must be trained on effective delivery. Ennis and colleagues (2019b) identified coaching techniques to increase BSP delivery, including in-person feedback, emailed performance feedback, visual performance feedback, BIE technology, and self-coaching techniques. Zoder-Martell and colleagues (2019) added coaching categories to include didactic, feedback, goal setting, in vivo, prompts, self-monitoring, and teacher incentive.…”
Section: Bspmentioning
confidence: 99%